Lectora Inspire in Learning Congruence Triangles in Higher Education - Sanwidi, Ardhi; Swastika, Galuh Tyasing (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2018)
The purpose of this study was to determine the use of Lectora Inspire assisted learning, analyze student activities in the learning process, and to find out the improvement of student achievement in triangular congruence material. This study uses an Action Research approach. The study uses two learning cycles. The results of this study are the use of Lectora Inspire assisted learning can increase student activity in the learning process of triangular congruence material. This can be seen from the percentage of student activity from 72.85% to 81.25%. In addition, this learning activity can improve student achievement. This can be seen from the increase in completeness percentage of student learning outcomes from 53.1% to 78.1%.